Tower-based CSP Artificial Light Calibration System. (May 2015) - Zavodny, M.; Slack, M.; Huibregtse, R.; Sonn, A.
Abstract: eSolar provides a low-cost, modular heliostat field solution for tower-based CSP facilities. Industry-leading cost has been achieved via large quantities of small (∼2.2 m2) single-facet, individually-controlled heliostats with simple field installation methods. These modular fields can contain up to 50, 000 heliostats (108, 000 m2) per receiver and a dozen or more modules may comprise a single plant, presenting a challenge for timely commissioning and calibration with previously existing technology. In response to this challenge, eSolar has developed a fully-automated proprietary calibration system that enables accurate individual heliostat tracking rapidly upon commissioning. The system operates by reflecting light from LEDs located on towers around the field into cameras, which are located on the same towers. The efficacy of this approach is demonstrated at eSolar's Sierra SunTower facility in Lancaster, CA, USA (Fig. 1) where a field of >24, 000 heliostats can be calibrated from realistic seed conditions in less than two weeks with resultant pointing error of <1.5 mrad. The calibration system's precise, parallel, and high throughput data collection further enables rapid detection of broken and mis-pointing heliostats, dramatically reducing the Mean Time to Repair (MTTR) from individual heliostat failures, as well as automating the task of discovering such failures. This paper describes the technical solution that eSolar has created and elaborates on the benefits of the system.